METODE DALAM MENCAPAI KESUFIAN (Perkembagan Tasawuf dan Maqamat dalam ilmu Tasawuf) - Ahmad Badwi (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
Sufism is generally an attitude thet always maintain personal purity, worship, live simply, willing to sacrifice for the good and always be medest.To obtain degrees as Sufi (degrees higher in purity) according mysticism is through several station, among others, we even do ascetic, repentance, wara’, powertu, patience, resignation and pleasure.